ANALISIS PERBAIKAN VARIABILITAS KUALITAS PRODUK DONAT PADA UKM DONAT RAFAEL - Tarihoran, Maya; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2024)
Rafael Donut UKM is one of the small businesses that produce donuts with various kinds of toppings, along with the business of donut products experiencing problems, namely the high variability rate, so it is necessary to conduct research to reduce the product variability rate. The methods used to analyze variability, namely with Six Sigma and Taguchi Method to design quality improvements, are carried out by making Taguchi experiment designs as the right and optimal parameters. The parameter design used in this study is an orthogonal array matrix 16 with four level designs and five influencing factors. The results of the study show that these five factors can affect the variability number and design proposals generated from the Taguchi experiment based on the SNR of the effects, namely A4, B4, C4, D4 and E4. Based on research, it shows that product quality variability requires quality parameters to be designed to maintain the expected product quality